2019
DOI: 10.1111/apa.14724
|View full text |Cite
|
Sign up to set email alerts
|

Increase in tympanostomy tube placements despite pneumococcal vaccination, a population‐based study

Abstract: Aim The aim was to estimate the impact of the 10‐valent pneumococcal vaccine (PHiD‐CV) on tympanostomy tube placements (TTP) in children under five years of age in Iceland. Methods This population‐based observational cohort study followed 11 consecutive birth‐cohorts 2005–2015 from birth until their fifth birthday. Population registries were merged using national identification numbers. The risk of TTP was compared between birth‐cohorts adjusted for the number of previous otitis media diagnoses and antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…One hundred and seventy‐eight abstracts were selected, and 165 full‐text articles were reviewed. After meticulous reading and discussion, 27 studies 3,4,7,10‐33 were included in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred and seventy‐eight abstracts were selected, and 165 full‐text articles were reviewed. After meticulous reading and discussion, 27 studies 3,4,7,10‐33 were included in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…One study 11 reported a greater reduction in the number of tympanostomy tube insertions in the PCV13 group than in the PCV7 group (HR, 0.76; 95% CI, 0.72‐0.80). One study 10 reported no significant decrease in the rate of tympanostomy tube insertion between the pre‐PCV10 and post‐PCV10 periods (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In OM, studies using large data resources (e.g. hospital and government datasets) are emerging, including linkage of medical presentation and management data, such as emergency room and primary health care presentations for OM [140], records of grommet insertions after vaccination program implementation [141], and records of grommet insertions in health insurance databases [142]. In these settings, comprehensive conclusions can only be drawn where quality data exist and are managed by a centralised tool.…”
Section: Advances Towards Om Microbiome Meta-analysesmentioning
confidence: 99%
“…Eythorsson et al. report that the incidence of ear tube insertions increased in Iceland after the introduction of the pneumococcal vaccine into the paediatric vaccination programme in 2011 . The reasons for these findings are speculative.…”
Section: Increase In Ear Tube Insertions Despite Pneumococcal Vaccinamentioning
confidence: 99%